Advances in Wireless and Mobile Communication Networks : A Multi-Layer Analysis - El Hammani, Sihame (Université Mohammed V, Faculté des sciences-Rabat, 2015)
The aim of this thesis is to provide the reader with a comprehensive view of the advances in wireless and mobile communication networks, while adopting a multi-layer analysis. We rely on TCP/IP architecture, and by browsing layers we try to cover different aspects of analysis, design, and optimization problems for heterogeneous wireless networks. We are more particularly interested in the physic, link and application layers that are very important, play a major role and have a great influence in the system performances. In the physical layer, we study and analyse the performance of two new technologies. Firstly, the wireless metropolitan area network (MAN) illustrated in WiMAX technology. And secondly, femtocell technology as special class of small cells, that can cover small areas with low power transmission which has become increasingly important for the indoor areas. Furthermore, as the choice of medium access control (MAC) protocol can affect the system performance and the use of wireless networks, we investigate one of the most popular random accesses MAC protocols, illustrated on slotted aloha protocol that affects directly the interoperability and the global roaming of mobile users. And finally, we focus on a practical case in the application layer by addressing the minimization of content diffusion time problem in social networks.
Keywords: WiMAX; Femtocells; Slotted Aloha; Social networks; Game theory; Learning algorithms; TCP/IP architecture; Performance Evaluation